OP022 Rapidity of clinical and laboratory improvements following upadacitinib induction treatment: data from the CELEST study. (16th January 2018) - Schreiber, S; Peyrin-Biroulet, L; Boland, B; Higgins, P D; Armuzzi, A; Terdiman, J; Zhou, W; Alperovich, G; Cataldi, F; Goteti, S; Lacerda, A P
Abstract: Background: The efficacy and safety of upadacitinib (UPA), an oral JAK1 inhibitor, were assessed in a 16-week induction study of patients with moderate to severe Crohn's disease (CD) and inadequate response/intolerance to an immunomodulator or tumour necrosis factor antagonist. 1 This analysis evaluates the rapidity of clinical remission, clinical response, and changes in markers of inflammation during the induction phase of CELEST. Methods: Adult patients with CD Activity Index (CDAI) 220-450, average daily liquid/very soft stool frequency (SF) ≥2.5 or daily abdominal pain score (AP) ≥2.0, and simplified endoscopic score for CD (SES-CD) ≥6 (or ≥4 for those with isolated ileal disease), were randomised to double-blind therapy with placebo (PBO) or immediate release formulation of UPA 3, 6, 12, 24 mg twice daily (BID), or 24 mg once daily (QD) for 16 weeks. Patients were randomised at baseline (BL) for follow-up ileocolonoscopy at either Week 12 or 16. The proportion of patients with modified clinical remission, enhanced clinical response, both defined in Figure, mean change from BL in high-sensitivity C-reactive protein (hsCRP) and faecal calprotectin (FC) were assessed in all patients unless otherwise mentioned. Comparisons between each UPA dose with PBO was tested by a Cochran–Mantel-–Haenszel test stratified by SES-CD at BL. Non-responder imputation was applied to patients who received open-label UPA or prematurely discontinued prior to Week 16 or initiated corticosteroid or had a corticosteroid dose increase higher than BL. Results: A total of 220 patients were enrolled (mean age 40.7 ± 12.9 years, CDAI 302.8 ± 63.4, CD duration 13.2 ± 10.0 years). Overall, patients receiving UPA achieved modified clinical remission as early as Week 4 and achieved enhanced clinical response at Week 8 compared with PBO. Over time, both clinical endpoints were sustained in all dose groups for up to 16 weeks with variable statistical significance likely due to small sample size (Figure A and B). Mean CRP levels significantly decreased in all UPA doses at Week 2 and were sustained for up to 16 weeks in the 12 and 24 mg BID and 24 mg QD arms (Figure C). Statistically significant decrease in mean FC from BL was observed with UPA at 12 and 24 mg BID at Week 4 and 24 mg BID at Week 16. Conclusions: Early and significant effects of upadacitinib in clinical parameters were demonstrated in a refractory patient population with active Crohn's disease, concurrent with a rapid and sustainable decrease in the markers of inflammation CRP and faecal calprotectin. Reference: 1. Sandborn WJ et al. Gastroenterology 2017;152(Suppl 1):S1308–9.